Development of Smart Fertigation System for Chili Plantation in Greenhouse Environment - Yap, Zheng Yang; Abd Rahman, Ramhuzaini (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This report presents the development and evaluation of a smart fertigation system tailored for chili plantation within a greenhouse environment, aimed at optimizing soil moisture levels to enhance agricultural efficiency. The system employs a NodeMCU ESP8266 development board to interface with a Blynk server, enabling real-time monitoring and control through a smartphone application. Key components include capacitive soil moisture sensors, a DHT22 temperature and humidity sensor, an L298N motor driver, and a 12V DC water pump. The system utilizes both Bang-Bang and Proportional Integral Derivative (PID) controllers to regulate irrigation based on precise soil moisture measurements. Through trial and error, the optimal PID parameters were determined as Kp = 7.2, Ki = 4, and Kd = 1, achieving a steady-state error of 1.24% and a rise time of 5.4 seconds. When the soil moisture level drops below 50%, the system automatically activates the irrigation pump and sends a notification to the user's smartphone. The integration of IoT technology with traditional irrigation methods demonstrates significant improvements in maintaining soil moisture, thereby promoting faster plant growth and reducing the risk of overwatering.